ANALISIS PENDAPATAN PETANI KAKAO DI DESA PANCAKARSA II KECAMATAN TALUDITI KABUPATEN POHUWATO (Studi Kasus Desa Pancakarsa II Kecamatan Taluditi Kabupaten Pohuwato) - Masni Masni; Yuriko Boekoesoe; Yanti Saleh (Agrinesia: Jurnal Ilmiah Agribisnis, 2016)
This research aims at (1) Investigating cost structure of cacao farm in Village of Pancakarsa II, Sub-district of Taluditi, District of Taluditi, District of Pohuwato by applying survey method. This research was done from June to July 2016. Data are analyzed descriptive qualitatively. Research findings are: (1) Cost of Cacao farm in Village of Pancakarsa II, Sub-district of Taluditi, District of Pohuwato is divided into two which are fixed cost and variable cost. Fixed cost consists of depreciation of tool and land tax, variable cost consists of seed, fertilizer, medicine and working cost; and (2) The highest total cost during 5 years of doing cacao farm is in 2015 which is Rp. 1.504.040 and the smallest is in 2012 which is Rp. 273.980. Mean, the highest income during 5 years of doing cacao farm is in 2015 which is Rp. 9.720.000 and the lowest is in 2012 which is Rp. 6.917.400. (2) The average income of Cacao farm in Village of Pancakarsa II, Sub-district of Taluditi, District of Pohuwato are Rp. 6.316.424 in 2011; Rp. 5.643.420 in 2012; Rp. 7.148.823. in 2013; Rp. 6.532.542 in 2014 and Rp. 8.213.137 in 2015. Therefore, the highest incomes is in 2015 which is Rp. 8.213.137 the lowest is in 2012 which is Rp. 5.643.420. Keywords: Cost of Farm, Income of Farmer